A highly-compact and ultra-fast homogeneous electromagnetic calorimeter based on oriented lead tungstate crystals - Bandiera, L.; Baryshevsky, V. G.; Canale, N.; Carsi, S.; Cutini, S.; Davì, F.; De Salvador, D.; Gianoli, A.; Guidi, V.; Haurylavets, V.; Korjik, M.; Lobko, A. S.; et al. (Frontiers in Physics, 2023)
Progress in high-energy physics has been closely tied to the development of high-performance electromagnetic calorimeters. Recent experiments have demonstrated the possibility to significantly accelerate the development of electromagnetic showers inside scintillating crystals typically used in homogeneous calorimeters based on scintillating crystals when the incident beam is aligned with a crystallographic axis to within a few mrad. In particular, a reduction of the radiation length has been measured when ultrarelativistic electron and photon beams were incident on a high-Z scintillator crystal along one of its main axes. Here, we propose the possibility to exploit this physical effect for the design of a new type of compact e.m. calorimeter, based on oriented ultra-fast lead tungstate (PWO-UF) crystals, with a significant reduction in the depth needed to contain electromagnetic showers produced by high-energy particles with respect to the state-of-the-art. We report results from tests of the crystallographic quality of PWO-UF samples via high-resolution X-ray diffraction and photoelastic analysis. We then describe a proof-of-concept calorimeter geometry defined with a Geant4 model including the shower development in oriented crystals. Finally, we discuss the experimental techniques needed for the realization of a matrix of scintillator crystals oriented along a specific crystallographic direction. Since the angular acceptance for e.m. shower acceleration depends little on the particle energy, while the decrease of the shower length remains pronounced at very high energy, an oriented crystal calorimeter will open the way for applications at the maximum energies achievable in current and future experiments. Such applications span from forward calorimeters, to compact beam dumps for the search for light dark matter, to source-pointing space-borne γ-ray telescopes, to decrease the size and the cost of the calorimeter needed to fully contain e.m. showers initiated by GeV to TeV particles.